Occurrence of Regulated and Emerging Iodinated DBPs in the Shanghai Drinking Water - Wei, Xiao (Public Library of Science, 2013)
Drinking water chlorination plays a pivotal role in preventing pathogen contamination against water-borne disease. However, chemical disinfection leads to the formation of halogenated disinfection by products (DBPs). Many DBPs are highly toxic and are of health concern. In this study, we conducted a comprehensive measurements of DBPs, including iodoacetic acid (IAA), iodoform (IF), nine haloacetic acids and four trihalomethanes in drinking waters from 13 water plants in Shanghai, China. The results suggested that IAA and IF were found in all the water treatment plants, with maximum levels of 1.66 µg/L and 1.25 µg/L for IAA and IF, respectively. Owing to deterioration of water quality, the Huangpu River has higher IAA and IF than the Yangtze River. Our results also demonstrated that low pH, high natural organic matter, ammonia nitrogen, and iodide in source waters increased IAA and IF formation. Compared to chlorine, chloramines resulted in higher concentration of iodinated DBP, but reduced the levels of trihalomethanes. This is the first study to reveal the widespread occurrence of IAA and IF in drinking water in China. The data provide a better understanding on the formation of iodinated disinfection byproducts and the findings should be useful for treatment process improvement and disinfection byproducts controls.